Introducing peer support work in Latin American mental health services - Peter Stastny (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2012)
In the course of implementing a recently funded network of hubs for building capacities in mental health service development, training, and research (RedeAmericas), the peer support workers are being introduced into the mental health workforce in three Latin American countries for the very first time. They will be part of a team, along with community mental health workers, that provides a modified Critical Time Intervention to individuals with severe psychiatric disorders living in the community. This article reviewed the background of this increasingly widespread development, and discussed its merits, as well as potential obstacles within local contexts.